THE IMPACT OF SOCIAL MEDIA ON THE GLOBAL SPREAD OF ENGLISH - Kuziyeva O.O, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION: This  article  examines  the  impact of  social  media  on  the  global spread of  the English  language. In  the  modern  era,  platforms  such as  Instagram,   YouTube, and  Twitter  have  become  powerful tools  not  only  for  communication  but  also  for  language  learning  and  dissemination.  The study  analyzes  how  social media  accelerates  the  adoption  of  English  as  a  global lingua franca,  reshapes traditional  language  learning  methods,  and  influences  non-native  speakers worldwide. The article  also  addresses  the  potential  negative  consequences, including  the  spread of  informal  language,  grammatical  errors, and  the  gradual displacement  of native  languages. The  findings  suggest that while social media significantly    contributes  to  the  global    dominance  of    English,  formal  education remains    essential    in    maintaining    linguistic  standards  and    preserving  linguistic diversity.